The Influence of Customer Relationship Management on Customer Satisfaction - Ridwan; Yuswari Nur; Mariah (Jurnal Economic Resource, 2021)
This study aims to examine and examine the effect of Customer Relationship Management through continuity marketing, one-to-one marketing, and partnering programs on customer satisfaction at the Makassar Employment Social Security Administration Office. This study uses a questionnaire as a data collection tool. Determination of the number of samples using Slovin's theory with calculations as many as 100 respondents. Furthermore, data analysis was carried out using descriptive qualitative analysis, research instrument testing (consisting of validity and reliability tests), classical assumption test (consisting of normality test, multicollinearity test, and heteroscedasticity test), multiple regression analysis, and hypothesis testing (consisting of partial test and simultaneous test). The results showed that Customer Relationship Management through Continuity Marketing, One to One Marketing, and Partnering Programs had a significant and simultaneous effect on customer satisfaction at BPJS Ketenagakerjaan in Makassar. Through this research, the BPJS Employment Office in Makassar must focus more on Sustainable Marketing in increasing customer loyalty and satisfaction by developing service innovations that have long-term benefits.